Experimental Investigation of Crack Initiation and Growth in Concrete Slabs Placed Directly on Clayey Soil (Journal of Engineering, 2022)
The main objective of this study is to examine the impact of moisture concrete of clayey soil on the concrete slabs placed directly over it. This experimental study presents the mechanical properties of the concrete slab when placed on different clayey soil moisture content ranging from 0% to the optimum moisture content of 35%. The tests were performed on soil concrete specimens of 25*30*50 mm exposed to sprayed water curing conditions for 28 days. Tests of compressive strength, ultrasonic pulse velocity, crack depth and crack width were investigated through this paper. An ejection relationship between compressive strength of concrete and water content in the soil was observed, with a 26% increase with water increasing from 0% to 35%. The opposite was observed in the ultrasonic pulse velocity test, with a decrease of 58% from 0% to the highest water content ratio. As for crack depth and width, it recorded the highest depth and lowest width at 0% water content due to the increased susceptibility of the soil to the absorption of water from the concrete when it’s totally dry. The experiment has shown that the soil moisture content is considered as a critical factor in controlling concrete cracking, and its variation has considerable implications for concrete crack growth.